Red clay mineral deposits I, prospecting, testing and evaluation - Ibarra, Ephraim E. (2000)
Red clay minerals of known and unknown deposits in the provinces of Mindanao were evaluated using the direct or residue method of testing red clays for possible ceramic ware productions. The amount of sample residue were determined by screening one kilogram of dried clay, passing through a 74micron (200 mesh) screen. Clays containing less than 20 percent sand residue were added with river sand. Clay samples were formed into a body using the soft mud method, molding in a 22 x 6 x 1.5 cm 2.5 x 2.5 x4 cm metal mold, dried in the air for a week, in an oven at 110℃ overnight and fired at 750℃, 850℃, 95℃, 1050℃, and 1150℃. Physical properties such as tempering water, drying shrinkage, firing shrinkage compressive strength, modulus of rupture, water absorption and porosity were measured. Results showed that red-clay ceramic products were satisfactorily produced in clays containing more than 20 weight percent strong sand residue and in clays added with river sand. The amount of sand residue ranged from 5-41 weight percent, water of plasticity ranged from 21 to 33 percent, drying shrinkage ranged from 6.77 to 16.95 percent. The firing shrinkage increased with the firing temperature in almost all the samples. Compressive strength gradually increased from 750 to 850℃, decreased from 850 to 950℃ and again increased at 1050℃. Water absorption decreased with increasing firing temperature. Modulus of rupture generally decreased above 850℃, and at 950℃ some of the samples exhibited an increase in MOR while many of the samples continued to decrease in their values.
Keywords: Ceramics; Red clay; Red clay ceramic; Mindanao studies